Double heterozygous pathogenic mutations in KIF3C and ZNF513 cause hereditary gingival fibromatosis - Jianfan Chen; Xueqing Xu; Song Chen; Ting Lu; Yingchun Zheng; Zhongzhi Gan; Zongrui Shen; Shunfei Ma; Duocai Wang; Leyi Su; Fei He; Xuan Shang; et al. (Nature Publishing Group, 2023)
Abstract Hereditary gingival fibromatosis (HGF) is a rare inherited condition with fibromatoid hyperplasia of the gingival tissue that exhibits great genetic heterogeneity. Five distinct loci related to non-syndromic HGF have been identified; however, only two disease-causing genes, SOS1 and REST, inducing HGF have been identified at two loci, GINGF1 and GINGF5, respectively. Here, based on a family pedigree with 26 members, including nine patients with HGF, we identified double heterozygous pathogenic mutations in the ZNF513 (c.C748T, p.R250W) and KIF3C (c.G1229A, p.R410H) genes within the GINGF3 locus related to HGF. Functional studies demonstrated that the ZNF513 p.R250W and KIF3C p.R410H variants significantly increased the expression of ZNF513 and KIF3C in vitro and in vivo. ZNF513, a transcription factor, binds to KIF3C exon 1 and participates in the positive regulation of KIF3C expression in gingival fibroblasts. Furthermore, a knock-in mouse model confirmed that heterozygous or homozygous mutations within Zfp513 (p.R250W) or Kif3c (p.R412H) alone do not led to clear phenotypes with gingival fibromatosis, whereas the double mutations led to gingival hyperplasia phenotypes. In addition, we found that ZNF513 binds to the SOS1 promoter and plays an important positive role in regulating the expression of SOS1. Moreover, the KIF3C p.R410H mutation could activate the PI3K and KCNQ1 potassium channels. ZNF513 combined with KIF3C regulates gingival fibroblast proliferation, migration, and fibrosis response via the PI3K/AKT/mTOR and Ras/Raf/MEK/ERK pathways. In summary, these results demonstrate ZNF513 + KIF3C as an important genetic combination in HGF manifestation and suggest that ZNF513 mutation may be a major risk factor for HGF.